Analisis Akuntansi Pajak Penghasilan (PPh) Pasal 22 Atas Impor Barang Pada PT Indika Tirta Mandiri - Nita Mustika (LPPM-STPI, 2022)
This study aims to determine how the accounting application of Income Tax (PPH) Article 22 on the Import of Goods at PT. Indika Tirta Mandiri, is it in accordance with the applicable tax laws. This research is a descriptive qualitative research, the research data obtained by direct observation (observation) interviews at the company that became the object of research, then analyzed and further processed. From the results of the study it can be concluded that the calculation and deposit of Article 22 Income Tax (Pph) at PT Indika Tirta Mandiri is in accordance with the applicable Tax Law and PT. Indika Tirta Mandiri has carried out accounting in accordance with PSAK.